2015
DOI: 10.1080/01635581.2015.1004730
|View full text |Cite
|
Sign up to set email alerts
|

L-Arginine Pretreatment Reduces Intestinal Mucositis as Induced by 5-FU in Mice

Abstract: Beneficial effects of L-arginine on immune responses and bowel function have been reported. Mucositis is a side effect of chemotherapy treatment that affects approximately 40% of patients. This complication is characterized by inflammation that affects the gastrointestinal tract, increasing permeability and causing abdominal pain, nausea, vomiting, and diarrhea, which worsen the patient's nutritional status and increases morbimortality. The aim of this study was to evaluate the effect of pretreating with 2% L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 39 publications
1
19
1
Order By: Relevance
“…This is presumably due to the increased cell-turnover rate which is a characteristic feature of the small intestine[ 3 ]. The main histological findings of villus shortening and crypt disruption caused by 5-FU administration were typical, and in concordance with other studies[ 27 - 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…This is presumably due to the increased cell-turnover rate which is a characteristic feature of the small intestine[ 3 ]. The main histological findings of villus shortening and crypt disruption caused by 5-FU administration were typical, and in concordance with other studies[ 27 - 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…Inflammatory infiltration is a characteristic of mucositis, which is triggered by the increased adhesion molecules in intestinal endothelia that attract the circulating inflammatory cells including neutrophils, T lymphocyte cells, B lymphocyte cells to gather in the inflammatory sites (Erbeldinger et al, 2017 ; Kim et al, 2017 ). The inflammatory cells further accelerate the modification of tight junction, thereby increase intestinal permeability leading to the disruption of mucosal barrier (Leocádio et al, 2015 ). The elevated pro-inflammatory cytokines induced by 5-Fu have been shown to account for the loss of tight junction proteins of small intestine, such as occludin and claudin-1, and result in diarrhea (Patel et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Body weight, diarrhea and bloody stool of mice were recorded daily for the assessment of mucositis. Diarrhea grade was evaluated based on the consistency of stool, using the modified parameters as described previously (Leocádio et al, 2015 ): 0, normal; 1, slightly wet; 2, moderate wet; 3, loose; 4, watery stool. At the last day (day 7), the grade of blood stool was assessed by a commercial testing paper (BASO diagnostics Inc. China) with the following scores: 0, normal; 1, slight bleeding; 2, moderate bleeding; 3, severe bleeding; 4, visible bleeding.…”
Section: Methodsmentioning
confidence: 99%
“…The results changed according to the type or concentration of agent or substance used. Some studies showed that amino acids, such as arginine, glutamine and citrulline, can promote partial mucosal recovery after mucositis induction [ 43 – 45 ]. Probiotics and prebiotics have also been extensively studied in mucositis, but with controversial results [ 16 , 46 – 48 ].…”
Section: Discussionmentioning
confidence: 99%